Dehumanization and burden of care among caregivers of terminally ill patients - Ines Testoni (Open Medical Publishing, 2021)
This article considers the relationship between dehumanization, ontological representation of death, trust in physicians, and burden of care on the part of caregivers of terminally ill patients. One hundred informal caregivers (relatives and friends) of patients hospitalized in four hospice facilities in northern Italy were involved. Of these, 77% were primary caregivers (those who mostly helped the patient). All of the participants were given a questionnaire comprising the Caregiver Burden Inventory (CBI) to determine caregivers' burden in their roles, the *questionario post mortem (QPM)* (post mortem questionnaire) for the effectiveness of and their trust in the medical nursing team of palliative care services, the Testoni death representation scale (TDRS) to detect their ontological representations of death and the humanity attribution test (HAT) to investigate their attributions of humanity to terminally ill patients. Per the literature, the present results demonstrated higher burden levels for female caregivers and primary caregivers. In informal caregiving, the dehumanization of patients does not have any advantage in reducing the burden of care. Further studies are required to compare formal and informal caregivers concerning the effect of dehumanization.